High-Performance Pad Conditioning (HPPC) Arm for Augmenting CMP Performance. (3rd August 2020) - Khanna, Aniruddh J.; Kakireddy, Veera Raghava; Fung, Jason; Jawali, Puneet; Yamamura, Mayu; Baradanahalli Kenchappa, Nandan; Hariharan, Venkat; Redfield, Daniel; Bajaj, Rajeev
Abstract : Pad conditioning (PC) is one of the key aspects of a chemical mechanical polishing (CMP) process. PC is known to impact the material removal rates (MRR), within-wafer non-uniformity (WIWNU) of material removal rates, planarization, defects, and the overall cost of ownership of the CMP process. Herein, changes in the aggressiveness of a pad conditioning disk with usage and exposure to the slurry are determined using the novel high-performance pad conditioning (HPPC) arm. The changes in the PC sweep torque was correlated to the change in the aggressiveness of the PC disk with usage. Thereafter, the rate of drop in the PC torque was used to characterize a PC disk into different regimes such as stable and unstable regimes. The stable regime of a PC disk is defined as the one in which the rate of drop in the PC sweep torque i.e. change in the disk aggressiveness with usage is not significant. Further, it is demonstrated that it is possible to maintain stable MRR, WIWNU over a large number of wafers by using a PC disk in its stable regime, which in turn augments the stability of a CMP process.